Quality selection in young oak stands - L. Chroust (Journal of Forest Science, 2007)
The paper deals with an experiment that was established at Opočno Experimental Station of the Forest and Game Management Research Institute (CR) in an oak small pole stage in 1952 to test whether Schaedelin'âs (1942) tending method worked out for beech stands is suitable for oak stands. Development and growth of the oak stand without tending are analysed, and the influence of repeated positive selection and of definitive selection of target trees on the oak stand is described. The result of the 50-year experiment is that Schaedelin's tending method is suitable also for oak stands. However, it is rational only if the choice of candidates from the small pole stage is focused on vital straight trees.